Demolition of Province House on Washington Street, ca. 1922 - Unknown (Tufts Archival Research Center, 2005)
Elevated view of the demolition of Province House, located on Washington Street at Province Court and Province Street. Province House, 1679-1922; former residence of the British Royal Governor 2 11/16 x 4 5/8 Photographs